Dark Triad, Perceptions of Organizational Politics and Counterproductive Work Behaviors: The Moderating Effect of Political Skills - Baloch, Muhammad A.; Meng, Fanchen; Xu, Zefeng; Cepeda-Carrion, Ignacio; Danish,; Bari, Muhammad W. (Frontiers in Psychology, 2017)
The aim of this work focuses on the relationship among the Dark Triad (psychopathy, narcissism, and Machiavellianism), perceptions of organizational politics, political skills, and counterproductive work behavior. This study empirically tests the mediating role of perceptions of organizational politics in the relationship between the Dark Triad and counterproductive work behavior. Furthermore, the study investigates the moderating role of political skills in strengthening the link between the Dark Triad and the perceptions of organizational politics. A sample of 149 participants was randomly selected. To analyze the data of the present work, we employ a structural equation model using partial least square and PROCESS. From empirical findings, we imply an inference that perception of organizational politics partially mediates the Dark Triad’s influence on the counterproductive work behavior. Moreover, the results identify the moderating role of political skills in strengthening the link between the Dark Triad and the perceptions of organizational politics. Empirical findings suggest important policy implications for the hospitality industry.